Miniature as a hypothetical regulatory protein of the Bursicon/Rickets signaling cascade in the wing epithelia of Drosophila melanogaster - Bilousov, O.O.; Katanaev, V.L.; Kozeretska, I.A. (Вiopolymers and Cell, 2012)
Soon after eclosion, epithelial cells of the Drosophila wing undergo a number of the processes due to a release of the neurohormone bursicon and its further binding to the GPCR Rickets, collectively referred to as wing maturation. Here we propose hypothetical models of the interaction between extracellular Miniature, and also Dusky, proteins and proteins responsible for triggering of the wing maturation processes in Drosophila melanogaster. Keywords: bursicon, Rickets, Miniature, Dusky, wing maturation. Відразу після вилуплення з пупарію в крилі дрозофіли відбувається низка процесів під загальною назвою матурація, які запускаються нейрогормоном бурсиконом та його рецептором Rickets. В огляді представлено гіпотетичні моделі взаємодії білків позаклітинного матриксу Miniature, а також Dusky, які є необхідними як на ранніх стадіях формування крила, так і після вилуплення мухи, з білками, відповідальними за запуск процесів матурації крила у D. melanogaster. Ключові словаs: бурсикон, Rickets, Miniature, Dusky, матурація крила. Сразу после вылупления из пупария в крыле дрозофилы происходит ряд процессов под общим названием матурация, запускаемых нейрогормоном бурсиконом и его рецептором Rickets. В обзоре представлены гипотетические модели взаимодействия белков внеклеточного матрикса Miniature, а также Dusky, необходимых как на ранних стадиях формирования крыла, так и после вылупления мухи, с белками, ответственными за запуск процесов матурации крыла у D. melanogaster. Ключевые слова: бурсикон, Rickets, Miniature, Dusky, матурация крыла.